PENGARUH DOMINAN E-GOVERNMENT QUALITY BERBASIS APLIKASI DISDUKCAPIL TERHADAP KEPUASAN MASYARAKAT KECAMATAN TANJUNG REDEB KABUPATEN BERAU - Sari, Vita Komala; Irawan, Bambang; Zulfiani, Dini (Magister Administrasi Publik FISIP Universitas Mulawarman, 2024)
The purpose of this research is to identify the indicators of e-government quality that mostly affect the people satisfaction on using the Disdukcapil Berau app at Berau, Tanjung Redeb regency. The research method used in this research is associative research with quantitative approach. Therefore the variables about e-government quality used in this research are: Content, Privacy, Usability, Quality, Accesibility, and Citizen engagement. The variables of people satisfaction in this reseach are: Terms,System, mechanism and procedur, Finishing time, Cost/fee,Competent and administrator habit, Report handling, feedback and suggestion, and Facilities and infrastructure. Data collecting method use is online survey which is googleform, literatur research and documentation with sampling method by doing proportional sampling from the apps user at Tanjung Redeb regency which is managed to get 99 responder. Analysis testing using validity test and reliability test, and standardized coefficients with the help of SPSS apps for windows v25. The result of the research can be said that the indication of e-government quality which mostly affect the people’s satisfaction is quality with a 0,330 value.